Pressure-sensitive adhesive composition, pressure-sensitive adhesive film, surface protection film for polarizing plate, and optical film with pressure-sensitive adhesive layer
Patent Information
- Application Number
- JP2023127100
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-13
- Estimated Expiration
- 2037-04-28
AI Technical Summary
【0022】 本発明によれば、優れた帯電防止性能と、耐汚染性とを両立することが可能な粘着剤組成物、及び表面保護フィルムを提供することができる。 本発明に係わる粘着剤組成物、及びそれを用いた表面保護フィルムは、被着体が、光学フィルムの表面に積層された、フッ素化合物を含有する防汚層、又は、フッ素化合物を含有する低屈折率層形成用の組成物を用いて形成された低屈折率層を有する被着体である場合において、従来技術に比べて、優れた耐汚染性を有し、且つ、経時劣化しないで優れた剥離帯電防止性能を有する。 すなわち、本発明に係わる粘着剤組成物、及びそれを用いた表面保護フィルムは、優れた帯電防止性能と、耐汚染性とを備えているため、産業上の利用価値が極めて大である。
Smart Images

Figure 0007629488000001 
Figure 0007629488000002 
Figure 0007629488000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a pressure-sensitive adhesive composition containing an antistatic agent, and a surface protective film. More specifically, the present invention relates to a pressure-sensitive adhesive composition containing an ionic compound having a specific sulfonate anion, such as nonafluorobutanesulfonate, as an antistatic agent, and thus to a pressure-sensitive adhesive composition having excellent antistatic performance and contamination resistance, and a surface protective film using the same. [Background technology]
[0002] Conventionally, in the manufacturing, processing, and assembly processes of precision parts and components such as electronic device parts, optical device parts, and image display panels, surface protection films have been affixed to the surfaces of these precision parts and components to temporarily protect the surfaces of these precision parts and components and to prevent the adhesion of particle and gaseous contaminants from the working environment and the occurrence of scratches and dents. For example, surface protection films used in the process of manufacturing optical components such as polarizing plates and retardation plates, which are components that make up liquid crystal displays, have an adhesive layer formed on one side of an optically transparent polyethylene terephthalate (PET) resin film, and a release film that has been treated to peel off in order to protect the adhesive layer is attached on top of the adhesive layer until it is attached to the optical component.
[0003] In addition, optical components such as polarizing plates and retardation plates are subjected to product inspection involving optical evaluation of the display performance, hue, contrast, and inclusion of foreign matter of the liquid crystal display panel with a surface protection film attached, so the required performance of the surface protection film is that the adhesive layer must be free of air bubbles and foreign matter. Moreover, in recent years, when peeling off a surface protection film from an optical component such as a polarizing plate or a retardation plate, there has been concern that peeling charge generated by static electricity generated when the adhesive layer is peeled off from the adherend may affect failure of the electrical control circuit of the liquid crystal display, and therefore there is a demand for adhesive layers with excellent antistatic performance. Thus, in recent years, the performance requirements for the pressure-sensitive adhesive layer constituting the surface protection film include excellent antistatic performance and antifouling performance from the viewpoint of ease of use when using the surface protection film.
[0004] Regarding excellent antistatic performance, a method of kneading an antistatic agent into a base film has been disclosed as a method for imparting antistatic properties to a surface protective film. Examples of the antistatic agent disclosed include: (a) various cationic antistatic agents having a cationic group such as a quaternary ammonium salt, a pyridinium salt, or a primary to tertiary amino group; (b) anionic antistatic agents having an anionic group such as a sulfonate group, a sulfate group, a phosphate group, or a phosphonate group; (c) amphoteric antistatic agents such as amino acid-based and amino sulfate-based agents; (d) nonionic antistatic agents such as amino alcohol-based, glycerin-based, and polyethylene glycol-based agents; and (e) polymer-type antistatic agents obtained by increasing the molecular weight of the above-mentioned antistatic agents (Patent Document 1). In recent years, it has been proposed to incorporate such antistatic agents into the base film, or to incorporate them directly into the pressure-sensitive adhesive layer rather than coating the surface of the base film (Patent Document 2). [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 11-070629 [Patent Document 2] JP 2000-129235 A Summary of the Invention [Problem to be solved by the invention]
[0006] Incidentally, in the case of surface protection films used for optical films such as LR (Low Reflective) polarizing plates and AG (Anti Glare)-LR polarizing plates, the surface of the optical film is subjected to anti-fouling treatment or low-reflection surface treatment using silicone compounds, fluorine compounds, etc., and therefore the peeling electrification voltage becomes high when the surface protection film used for such optical films is peeled off from the substrate.
[0007] Furthermore, for pressure-sensitive adhesive compositions with antistatic properties, and for surface protection films using such compositions, the relationship between the antistatic properties and the contamination resistance of the adherend is a trade-off, and it has been difficult to improve the contamination resistance while maintaining the antistatic properties. For this reason, in terms of pressure-sensitive adhesive compositions for surface protection films used on optical films such as LR polarizing plates and AG-LR polarizing plates, there is a demand for pressure-sensitive adhesive compositions that can reduce the peeling electrification voltage when the surface protection film is peeled off from the optical film and that cause little contamination of the adherend, even if the surface of the optical film has been treated with an anti-fouling treatment or a low-reflection surface treatment using a silicone compound, a fluorine compound, or the like.
[0008] The present invention has been made in consideration of the above circumstances, and aims to solve a new problem of providing a pressure-sensitive adhesive composition that can achieve both excellent antistatic performance and contamination resistance when an adherend is surface-treated with a composition containing a fluorine compound, and a surface protection film using the same. [Means for solving the problem]
[0009] The present inventors have created a new adhesive composition containing a copolymer in which the number of carbon atoms in the alkyl group of the alkyl (meth)acrylate constituting the acrylic polymer of the adhesive composition is limited to a specific range and two or more alkyl (meth)acrylates in a specific combination are copolymerized, and an antistatic agent consisting of an ionic compound having a melting point of 25° C. or more and a specific sulfonate anion, such as nonafluorobutanesulfonate. The inventors have found that this makes it possible to obtain an adhesive composition that has superior contamination resistance and excellent peel-off antistatic performance without deterioration over time, compared with conventional adhesive compositions for surface protection films, and have thus completed the present invention. In particular, when the adherend has an anti-fouling layer containing a fluorine compound, or a low refractive index layer formed using a composition for forming a low refractive index containing a fluorine compound, laminated on the surface of an optical film, the surface protective film of the present invention has superior contamination resistance compared to conventional techniques, and has excellent peel-off antistatic performance without deterioration over time, and has been found to be effective in achieving both antistatic performance and contamination resistance.
[0010] In order to solve the above problems, the present invention provides A pressure-sensitive adhesive composition comprising an acrylic polymer, an antistatic agent, and a crosslinking agent, The acrylic polymer is (A) at least two or more kinds of (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18, the total of (a1) and (a2) being 100 parts by weight, comprising: (a1) 1 to 50 parts by weight of at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4; and (a2) 50 to 99 parts by weight of at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C5 to C18. (B) at least one copolymerizable vinyl monomer containing a hydroxyl group; (C) at least one polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer, (However, acrylic polymers copolymerized with at least one of a nitrogen-containing vinyl monomer not containing a hydroxyl group or an alkoxy-containing alkyl (meth)acrylate monomer not containing a hydroxyl group are excluded.) Among the (a2), at least one selected from the group consisting of isooctyl (meth)acrylate, isononyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is contained in an amount of 50 parts by weight or more; The acrylic polymer has a glass transition temperature of 0° C. or less, the (D) crosslinking agent is a tri- or higher functional isocyanate compound, the antistatic agent is an ionic compound having a melting point of 25° C. or higher and composed of a cation and an anion, the anion being one selected from the group consisting of a trifluoromethanesulfonate anion, a pentafluoroethanesulfonate anion, a heptafluoropropanesulfonate anion, and a nonafluorobutanesulfonate anion; the pressure-sensitive adhesive composition further comprises (E) a crosslinking accelerator which is a metal chelate compound; and (F) a keto-enol tautomer compound; The pressure-sensitive adhesive composition is characterized in that it contains, as an essential component, the antistatic agent in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of the acrylic polymer.
[0011] The acrylic polymer is (A) at least two or more kinds of (meth)acrylic acid ester monomers having an alkyl group with a carbon number of C1 to C18, the total of (a1) and (a2) being 100 parts by weight, comprising: (a1) 1 to 50 parts by weight of at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4; and (a2) 50 to 99 parts by weight of at least one kind of (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C5 to C18. (B) at least one copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group, (C) at least one polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer, is an acrylic polymer of a copolymer obtained by copolymerizing Among the (a2), at least one selected from the group consisting of isooctyl (meth)acrylate, isononyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is contained in an amount of 50 parts by weight or more; It is preferable that the pressure-sensitive adhesive composition further contains (E) a crosslinking accelerator which is a metal chelate compound, and (F) a keto-enol tautomer compound.
[0012] The cation is preferably one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium.
[0013] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition has a surface resistivity of 1.0×10 +12 It is preferable that the peeling electrification voltage of the pressure-sensitive adhesive layer with respect to a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound is −0.3 to +0.3 kV.
[0014] the (B) copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group is at least one selected from the group consisting of copolymerizable monomers containing a hydroxyl group and copolymerizable monomers containing a carboxyl group, the hydroxyl group-containing copolymerizable monomer is at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, and N-hydroxyethyl(meth)acrylamide; The copolymerizable monomer containing a carboxyl group is preferably at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid.
[0015] the (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has an average repeat number of alkylene oxides constituting the polyalkylene glycol chain of 3 to 14, the (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has a diester content of 0.2% or less, It is preferable that the (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer contains at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate in an amount of 1 to 50 parts by weight per 100 parts by weight in total of the (A) at least two or more (meth)acrylic acid ester monomers having an alkyl group with a carbon number of 1 to 18.
[0016] the (E) crosslinking accelerator is at least one selected from the group consisting of an aluminum chelate compound, a titanium chelate compound, and an iron chelate compound, It is preferable that the (E) crosslinking accelerator is contained in an amount of 0.001 to 0.5 parts by weight and the (F) keto-enol tautomer compound is contained in an amount of 0.1 to 300 parts by weight relative to 100 parts by weight of the acrylic polymer, and the (F) / (E) weight part ratio is 70 to 1000.
[0017] The present invention also provides a pressure-sensitive adhesive film, comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition on one side of the resin film.
[0018] The present invention also provides a surface protection film using the above-mentioned pressure-sensitive adhesive film.
[0019] The present invention also provides a surface protection film for a polarizing plate, which uses the above-mentioned pressure-sensitive adhesive film.
[0020] The present invention also provides an optical film with a pressure-sensitive adhesive layer, comprising an optical film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition, laminated on at least one surface of the optical film.
[0021] The present invention also provides a pressure-sensitive adhesive film, wherein one surface of the resin film opposite to the surface on which the pressure-sensitive adhesive layer is laminated is subjected to an antistatic treatment and an antifouling treatment. Effect of the Invention
[0022] According to the present invention, it is possible to provide a pressure-sensitive adhesive composition and a surface protective film that can achieve both excellent antistatic performance and contamination resistance. The pressure-sensitive adhesive composition of the present invention and the surface protection film using the same have superior contamination resistance and excellent antistatic performance upon peeling without deterioration over time, compared to conventional techniques, when the adherend is an adherend having an anti-fouling layer containing a fluorine compound, or a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound, laminated on the surface of an optical film. That is, the pressure-sensitive adhesive composition of the present invention and the surface protection film using the same have excellent antistatic properties and stain resistance, and therefore are of extremely high industrial utility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the present invention will be described based on preferred embodiments. The pressure-sensitive adhesive composition of the present embodiment is a pressure-sensitive adhesive composition containing an acrylic polymer, an antistatic agent, and a crosslinking agent, wherein the acrylic polymer has a glass transition temperature of 0°C or lower, the (D) crosslinking agent is a tri- or higher functional isocyanate compound, the antistatic agent is an ionic compound composed of a cation and an anion and having a melting point of 25°C or higher, the anion being one selected from the group consisting of trifluoromethanesulfonate anion, pentafluoroethanesulfonate anion, heptafluoropropanesulfonate anion, and nonafluorobutanesulfonate anion, and the antistatic agent is contained as an essential component in a ratio of 0.01 to 10 parts by weight per 100 parts by weight of the acrylic polymer. The antistatic agent is preferably an ionic compound having a solid melting point of 25° C. or higher at a temperature of 25° C., and the melting point of the antistatic agent is preferably 450° C. or lower.
[0024] The acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment has a glass transition temperature of not more than 0° C. In addition, the acrylic polymer is preferably a copolymer mainly composed of (A) a (meth)acrylic acid ester monomer having an alkyl group with 1 to 18 carbon atoms.
[0025] In addition, (A) (meth)acrylic acid ester monomers having an alkyl group with a carbon number of 1 to 18 include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, isooctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, etc. The alkyl group of the alkyl (meth)acrylate monomer may be linear, branched, or cyclic.
[0026] In addition, the ratio of (a1) at least one kind of (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C4 is preferably 1 to 50 parts by weight, and (a2) at least one kind of (meth)acrylic acid ester monomer having an alkyl group carbon number of C5 to C18 is preferably 50 to 99 parts by weight, relative to a total of 100 parts by weight of (A) (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18. In addition, the ratio of at least one kind of (a2) selected from the group consisting of isooctyl (meth)acrylate, isononyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate is preferably 50 parts by weight or more, relative to a total of 100 parts by weight of (A) (meth)acrylic acid ester monomer having an alkyl group carbon number of C1 to C18.
[0027] The acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment can be copolymerized with at least one of (B) copolymerizable vinyl monomers containing a hydroxyl group and / or a carboxyl group as an optional component. (B) The copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group can be at least one selected from the group consisting of copolymerizable monomers containing a hydroxyl group (hydroxyl group-containing monomers) and copolymerizable monomers containing a carboxyl group (carboxyl group-containing monomers). That is, only either the hydroxyl group-containing monomer or the carboxyl group-containing monomer may be selected and copolymerized, or both the hydroxyl group-containing monomer and the carboxyl group-containing monomer may be copolymerized.
[0028] Examples of the hydroxyl group-containing monomer include at least one selected from the group consisting of 8-hydroxyoctyl(meth)acrylate, 6-hydroxyhexyl(meth)acrylate, 4-hydroxybutyl(meth)acrylate, 2-hydroxyethyl(meth)acrylate, N-hydroxy(meth)acrylamide, N-hydroxymethyl(meth)acrylamide, N-hydroxyethyl(meth)acrylamide, etc. The ratio of the hydroxyl group-containing monomer contained in the pressure-sensitive adhesive composition of the present embodiment is preferably 0.1 to 20 parts by weight, more preferably 4.1 to 16 parts by weight, and particularly preferably 5.1 to 14 parts by weight, relative to 100 parts by weight in total of at least two or more (meth)acrylic acid ester monomers (A) having an alkyl group with carbon number of C1 to C18.
[0029] Examples of the carboxyl group-containing monomer include at least one selected from the group consisting of (meth)acrylic acid, carboxyethyl (meth)acrylate, carboxypentyl (meth)acrylate, 2-(meth)acryloyloxyethyl hexahydrophthalic acid, 2-(meth)acryloyloxypropyl hexahydrophthalic acid, 2-(meth)acryloyloxyethyl phthalic acid, 2-(meth)acryloyloxyethyl succinic acid, 2-(meth)acryloyloxyethyl maleic acid, carboxypolycaprolactone mono(meth)acrylate, and 2-(meth)acryloyloxyethyl tetrahydrophthalic acid. The proportion of the carboxyl group-containing monomer in the pressure-sensitive adhesive composition according to this embodiment is preferably 0 to 5.0 parts by weight relative to 100 parts by weight in total of at least two or more (A) (meth)acrylic acid ester monomers having an alkyl group carbon number of C1 to C18 (the case where the carboxyl group-containing monomer is not copolymerized is also permissible), and when the carboxyl group-containing monomer is copolymerized, the proportion is more preferably 0.01 to 5.0 parts by weight, particularly preferably 0.02 to 1.3 parts by weight, and most preferably 0.02 to 0.8 parts by weight.
[0030] The acrylic polymer used in the pressure-sensitive adhesive composition of the present embodiment may be copolymerized with (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer as an optional component. The (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer may be a compound in which one of the multiple hydroxyl groups of a polyalkylene glycol is esterified as a (meth)acrylic acid ester. The (meth)acrylic acid ester group is a polymerizable group, so that it can be copolymerized with the acrylic polymer. In the present embodiment, even if the polyalkylene glycol mono(meth)acrylate has the other hydroxyl group as OH, it is not classified as (B) copolymerizable vinyl monomer containing a hydroxyl group and / or a carboxyl group. The (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer may be an alkoxy polyalkylene glycol mono(meth)acrylate in which the other hydroxyl group is converted to an alkyl ether.
[0031] The polyalkylene glycol constituting the polyalkylene glycol chain may be any glycol compound having one or more alkylene groups, and examples thereof include polyethylene glycol, polypropylene glycol, polybutylene glycol, polyethylene glycol-polypropylene glycol, polyethylene glycol-polybutylene glycol, polypropylene glycol-polybutylene glycol, and polyethylene glycol-polypropylene glycol-polybutylene glycol.
[0032] In addition, it is preferable that the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer (C) has an average repeat number of alkylene oxide constituting the polyalkylene glycol chain of 3 to 14. The "average repeat number of alkylene oxide" refers to the average number of repeating alkylene oxide units in the "polyalkylene glycol chain" portion contained in the molecular structure of the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer (C). In addition, it is preferable that the diester content in the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer (C) is 0.2% or less. The "diester content in the monomer" refers to the content (wt%) of polyalkylene glycol di(meth)acrylic acid ester contained in the polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer (C).
[0033] In addition, the (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer is preferably at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate. The proportion of (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer in the pressure-sensitive adhesive composition of this embodiment is preferably 1 to 50 parts by weight, more preferably 1 to 30 parts by weight, and particularly preferably 2 to 25 parts by weight, relative to 100 parts by weight in total of at least two or more (meth)acrylic acid ester monomers (A) having an alkyl group with carbon number of 1 to 18.
[0034] The method for producing the acrylic polymer contained in the pressure-sensitive adhesive composition according to the present embodiment is not particularly limited, and any known polymerization method such as solution polymerization, emulsion polymerization, etc. is usable as appropriate. In the pressure-sensitive adhesive composition according to the present embodiment, the weight-average molecular weight of the copolymer of the acrylic polymer used is preferably 1,000,000 to 3,000,000.
[0035] The pressure-sensitive adhesive composition according to the present embodiment contains an antistatic agent (G) in order to obtain antistatic properties. The antistatic agent (G) is an ionic compound having a melting point of 25°C or higher and composed of a cation and an anion, and the anion is a trifluoromethanesulfonate anion (CF3SO3 - ), pentafluoroethanesulfonate anion (CF3CF2SO3 - ), heptafluoropropanesulfonate anion (CF3CF2CF2SO3 - ), nonafluorobutanesulfonate anion (CF3CF2CF2CF2SO3 - The pressure-sensitive adhesive composition according to the present embodiment preferably contains, as an essential component, 0.01 to 10 parts by weight of an antistatic agent (G) relative to 100 parts by weight of an acrylic polymer, and further increases the antistatic performance of the pressure-sensitive adhesive layer to a lower limit of the surface resistivity of 1.0×10 +10 When it is necessary to reduce the resistivity to Ω / □ or less, it is more preferable to contain the (G) antistatic agent in an amount of 0.01 to 15 parts by weight.
[0036] In addition, the cation contained in the ionic compound may be one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium. Specific examples of the (G) antistatic agent include lithium trifluoromethanesulfonate, lithium nonafluorobutanesulfonate, 1-methyl-3-octylpyridinium trifluoromethanesulfonate salt, 3-methyl-1-octylpyridinium trifluoromethanesulfonate salt, 1-methyl-4-octylpyridinium nonafluorobutanesulfonate salt, 4-methyl-1-octylpyridinium nonafluorobutanesulfonate salt, dimethyldioctylammonium pentafluoroethanesulfonate salt, 1-methyl-3-octylpyridinium heptafluoropropanesulfonate salt, 3-methyl-1-octylpyridinium heptafluoropropanesulfonate salt, 1-methyl-3-octylpyridinium nonafluorobutanesulfonate salt, 3-methyl-1-octylpyridinium nonafluorobutanesulfonate salt, and 1-octyl-3-methylimidazolium. nonafluorobutanesulfonate salts.
[0037] The pressure-sensitive adhesive composition according to this embodiment further contains a tri- or higher functional isocyanate compound as a crosslinking agent (D). Examples of the trifunctional or higher isocyanate compound include biuret modified products and isocyanurate modified products of diisocyanates such as hexamethylene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, tolylene diisocyanate, and xylylene diisocyanate, and adducts with trivalent or higher polyols such as trimethylolpropane and glycerin. The proportion of the (D) crosslinking agent is, for example, 0.01 to 5 parts by weight per 100 parts by weight of the acrylic polymer.
[0038] The pressure-sensitive adhesive composition according to the present embodiment may contain (E) a crosslinking accelerator. When a polyisocyanate compound is used as a crosslinking agent, the (E) crosslinking accelerator may be any substance that functions as a catalyst for the reaction (crosslinking reaction) between the acrylic polymer and the crosslinking agent, and examples of the crosslinking accelerator include amine compounds such as tertiary amines, metal chelate compounds, organotin compounds, organolead compounds, organozinc compounds, and other organometallic compounds. In the present embodiment, the crosslinking accelerator is preferably a metal chelate compound.
[0039] Moreover, the metal chelate compound is a compound in which one or more polydentate ligands L are bonded to a central metal atom M. The metal chelate compound may or may not have one or more monodentate ligands X bonded to the metal atom M. For example, the general formula of a metal chelate compound having one metal atom M is expressed as M(L) m (X) n When m is 2 or more, m L's may be the same ligand or different ligands. When n is 2 or more, n X's may be the same ligand or different ligands.
[0040] Examples of the metal atom M include Fe, Ni, Mn, Cr, V, Ti, Ru, Zn, Al, Zr, and Sn. Examples of the polydentate ligand L include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone (also known as 2,4-pentanedione), 2,4-hexanedione, and benzoylacetone. These are keto-enol tautomer compounds, and in the polydentate ligand L, the enol may be deprotonated to form an enolate (e.g., acetylacetonate). Examples of the monodentate ligand X include halogen atoms such as chlorine and bromine atoms, acyloxy groups such as pentanoyl, hexanoyl, 2-ethylhexanoyl, octanoyl, nonanoyl, decanoyl, dodecanoyl, and octadecanoyl groups, and alkoxy groups such as methoxy, ethoxy, n-propoxy, isopropoxy, and butoxy groups.
[0041] Specific examples of metal chelate compounds include iron tris(2,4-pentanedionato)(III), iron trisacetylacetonate, titanium trisacetylacetonate, ruthenium trisacetylacetonate, zinc bisacetylacetonate, aluminum trisacetylacetonate, zirconium tetrakisacetylacetonate, iron tris(2,4-hexanedionato)(III), zinc bis(2,4-hexanedionato), titanium tris(2,4-hexanedionato), aluminum tris(2,4-hexanedionato), and zirconium tetrakis(2,4-hexanedionato).
[0042] The (E) crosslinking accelerator is preferably at least one selected from the group consisting of aluminum chelate compounds, titanium chelate compounds, and iron chelate compounds. The pressure-sensitive adhesive composition according to the present embodiment preferably contains the (E) crosslinking accelerator in a ratio of 0.001 to 0.5 parts by weight per 100 parts by weight of the acrylic polymer.
[0043] The pressure-sensitive adhesive composition according to the present embodiment may contain (F) a keto-enol tautomer compound. Examples of the (F) keto-enol tautomer compound include β-ketoesters such as methyl acetoacetate, ethyl acetoacetate, octyl acetoacetate, oleyl acetoacetate, lauryl acetoacetate, and stearyl acetoacetate, and β-diketones such as acetylacetone, 2,4-hexanedione, and benzoylacetone. In a pressure-sensitive adhesive composition using a polyisocyanate compound as a crosslinking agent, these compounds block the isocyanate groups of the crosslinking agent, thereby suppressing excessive viscosity increase and gelation of the pressure-sensitive adhesive composition after the crosslinking agent is blended, and thereby extending the pot life of the pressure-sensitive adhesive composition. The pressure-sensitive adhesive composition according to this embodiment preferably contains 0.1 to 300 parts by weight of the (F) keto-enol tautomer compound relative to 100 parts by weight of the acrylic polymer.
[0044] In addition, since the (F) keto-enol tautomer compound has an effect of suppressing crosslinking, contrary to the (E) crosslinking accelerator, it is preferable to appropriately set the ratio of the (F) keto-enol tautomer compound to the (E) crosslinking accelerator. In order to extend the pot life of the pressure-sensitive adhesive composition and improve the storage stability, the (F) / (E) weight parts ratio is preferably 70 to 1000, more preferably 70 to 700, and particularly preferably 80 to 600. Here, the (F) / (E) weight parts ratio is the quotient value obtained by dividing the parts by weight of (F) by the parts by weight of (E).
[0045] The adhesive composition of the present embodiment may contain, as appropriate, known additives such as antioxidants, surfactants, curing accelerators, plasticizers, fillers, curing retarders, processing aids, and antiaging agents, in addition to the additives described above. These may be used alone or in combination of two or more.
[0046] The pressure-sensitive adhesive layer obtained by crosslinking the pressure-sensitive adhesive composition of the present embodiment has a surface resistivity of 1.0×10 +12 It is preferable that the surface resistivity is 5.0×10 +11 More preferably, the surface resistivity is 2.0×10 +11 It is particularly preferable that the surface resistivity is Ω / □ or less. If the surface resistivity is large, the performance of dissipating static electricity generated by charging when peeling the pressure-sensitive adhesive layer from the adherend is poor. Therefore, by making the surface resistivity of the pressure-sensitive adhesive layer sufficiently small, the peeling electrification voltage caused by static electricity generated when peeling the pressure-sensitive adhesive layer from the adherend is reduced, and the influence on the adherend can be suppressed.
[0047] The adhesive layer crosslinked with the adhesive composition of the present embodiment preferably has a peeling electrification voltage of the adhesive layer relative to a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound within the range of -0.3 to +0.3 kV. Examples of the fluorine compound used in the composition for forming a low refractive index layer include fluorine-containing copolymers which are polymers of one or more of fluorinated olefins, fluorinated vinyl ethers, fluorinated alkyl (meth)acrylates, etc., and condensates of fluorinated alkyl group-containing silane compounds, etc. The fluorine-containing copolymer may be copolymerized with non-fluorinated monomers such as olefins, vinyl ethers, and (meth)acrylates in addition to fluorinated monomers. The low refractive index layer may be combined with a high refractive index layer, etc. to form an antireflection layer.
[0048] The adhesive film of the present embodiment is a film in which an adhesive layer crosslinked with the adhesive composition of the present embodiment is laminated on one side of a substrate film. The adhesive film of the present embodiment can be suitably used as a surface protection film, a surface protection film for a polarizing plate, or a surface protection film for an optical film. An optical film with an adhesive layer can be obtained by laminating an adhesive layer crosslinked with the adhesive composition of the present embodiment on at least one side of an optical film. Examples of optical films include polarizing films, retardation films, anti-reflection films, anti-glare films, ultraviolet absorbing films, infrared absorbing films, optical compensation films, and brightness enhancing films. Examples of devices to which optical members are applied include liquid crystal panels, organic EL panels, and touch panels.
[0049] As the base film of the pressure-sensitive adhesive layer and the release film (separator) that protects the adhesive surface, a resin film such as a polyester film can be used. The substrate film may be subjected to an antifouling treatment using a silicone-based or fluorine-based release agent or coating agent, or silica microparticles or an antistatic treatment by coating or kneading an antistatic agent on the side opposite to the side on which the pressure-sensitive adhesive layer of the resin film is formed. The surface of the release film that faces the adhesive surface of the adhesive layer is subjected to a release treatment using a silicone-based or fluorine-based release agent. In the case of an optical surface protection film such as a surface protection film for a polarizing plate, the base film and the pressure-sensitive adhesive layer preferably have sufficient transparency. EXAMPLES
[0050] The present invention will now be described in detail with reference to examples.
[0051] <Production of acrylic polymer> [Example 1] Nitrogen gas was introduced into a reactor equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, and the air in the reactor was replaced with nitrogen gas. Then, 12 parts by weight of methyl acrylate, 88 parts by weight of 2-ethylhexyl acrylate, 12.0 parts by weight of 8-hydroxyoctyl acrylate, 0.1 parts by weight of acrylic acid, 20 parts by weight of polypropylene glycol monoacrylate (average repeat number of alkylene oxide n = 12), and 100 parts of a solvent (ethyl acetate) were added to the reactor. Then, 0.1 parts by weight of azobisisobutyronitrile as a polymerization initiator was dropped over 2 hours, and the mixture was reacted at 65 ° C. for 8 hours to obtain an acrylic polymer solution of Example 1. [Examples 2 to 6 and Comparative Examples 1 to 3] Acrylic polymer solutions used in Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the acrylic polymer solution used in Example 1 above, except that the monomer compositions were as shown in Table 1.
[0052] <Production of Pressure-Sensitive Adhesive Composition and Surface Protective Film> [Example 1] To the acrylic polymer solution of Example 1 produced as described above, 2.0 parts by weight of a crosslinking agent (Coronate HX), 1.0 parts by weight of an antistatic agent (lithium nonafluorobutanesulfonate), 0.1 parts by weight of a crosslinking accelerator (titanium trisacetylacetonate), and 9 parts by weight of a ketoenol tautomer compound (acetylacetone) were added and mixed by stirring to obtain an adhesive composition of Example 1. This adhesive composition was applied onto a release film made of a silicone resin-coated polyethylene terephthalate (PET) film, and then dried at 90°C to remove the solvent, thereby obtaining an adhesive layer having a thickness of 20 μm. Thereafter, the adhesive layer with the release film was transferred onto the opposite side of the antistatic and antifouling treated surface of a base film made of polyethylene terephthalate (PET) that had been antistatic and antifouling treated on one side, to obtain a surface protection film of Example 1 having a laminated structure of base film / adhesive layer / release film. [Examples 2 to 6 and Comparative Examples 1 to 3] Surface protection films of Examples 2 to 6 and Comparative Examples 1 to 3 were obtained in the same manner as the surface protection film of Example 1 above, except that the compositions of the additives were as shown in Table 1.
[0053] [Table 1]
[0054] In Table 1, the parts by weight of each component were calculated assuming that the total of (a1) and (a2), which are (A) (meth)acrylic acid ester monomers having an alkyl group of 1 to 18 carbon atoms, is 100 parts by weight. In Table 1, in columns (D), (G), (E), and (F), the content (parts by weight) of each component is shown as a number in parentheses ( ), with the acrylic polymer being 100 parts by weight. The compound names of the abbreviations of each component used in Table 1 are shown in Table 2. Of the (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomers, C-1 to C-5 have a diester content of 0.2% or less in the monomer, and C-6 has a diester content of 0.8% in the monomer. G-1 to G-6 all have a melting point of 25°C or more and are ionic compounds that are solid at 25°C, and G-7 has a melting point of 15°C and is an ionic compound that is liquid at 25°C.
[0055] [Table 2]
[0056] Coronate (registered trademark) HX, Coronate (registered trademark) HL, and Coronate (registered trademark) L are product names of Tosoh Corporation, and D-127N and Takenate (registered trademark) D-140N are product names of Mitsui Chemicals, Inc. Also, HDI means hexamethylene diisocyanate, IPDI means isophorone diisocyanate, XDI means xylylene diisocyanate, TDI means tolylene diisocyanate, and TMP means trimethylolpropane.
[0057] <Test methods and evaluation> The surface protection films of Examples 1 to 6 and Comparative Examples 1 to 3 were each aged for 7 days in an atmosphere of 23° C. and 50% RH, and then evaluated by the following test method.
[0058] <Adhesive strength test method> The release film was peeled off to expose the adhesive layer, and the surface protection film was attached to the surface of a polarizing plate (a polarizing plate with a protective layer of a polarizer of TAC was used) via the adhesive layer, and the plate was left for one day, then autoclaved at 50°C and 5 atm for 20 minutes, and left at room temperature for another 12 hours to obtain a sample for measuring adhesive strength. The polarizing plate as the adherend was an LR polarizing plate or an AG-LR polarizing plate. The measurement sample obtained above was peeled off in the 180° direction using a tensile tester at a low speed (0.3 m / min) or a high speed (30 m / min), and the peel strength was measured and used as the adhesive strength. Here, in the above-mentioned LR polarizing plate and AG-LR polarizing plate, the surface of the polarizing plate is subjected to a low reflection surface treatment with a composition containing a fluorine compound.
[0059] <Surface resistivity test method> After aging the surface protection film and before bonding to the adherend, the release film was peeled off to expose the adhesive layer, and the surface resistivity of the adhesive layer was measured using a resistivity meter Hiresta UP-HT450 (manufactured by Mitsubishi Chemical Analytech).
[0060] <Test method for peeling electrification voltage> The release film was peeled off to expose the pressure-sensitive adhesive layer, and the surface protection film was attached to an adherend having a low refractive index layer formed on the adherend surface using a composition for forming a low refractive index layer containing a fluorine compound. When the surface protection film was peeled off at 180° at a tensile speed of 30 m / min, the voltage (charged voltage) generated by the adherend being charged was measured using high-precision static electricity sensors SK-035 and SK-200 (manufactured by Keyence Corporation), and the maximum measured value was taken as the peeling charged voltage.
[0061] <Test method for stain resistance> The LR polarizing plate that had been subjected to the low reflection surface treatment or the AG-LR polarizing plate that had been subjected to the low reflection surface treatment (a polarizing plate in which the protective layer of the polarizer is TAC) was attached to one side of a glass plate via an adhesive layer (double-sided adhesive tape) using a laminating machine. Then, a surface protective film was attached to the surface of the polarizing plate using a laminating machine. After storing for 3 days and 30 days under an environment of 23°C and 50% RH, the surface protective film was peeled off, and the contamination state of the surface of the polarizing plate was visually observed. The criteria for judging the contamination resistance were as follows: no contamination on the surface of the polarizing plate was evaluated as "○", slight contamination was evaluated as "△", and contamination was evaluated as "×".
[0062] Table 3 shows the evaluation results for the surface protection films in Examples 1 to 6 and Comparative Examples 1 to 3. The "surface resistivity" is expressed as "m×10 +n" is expressed as "mE+n" (where m is any real number and n is a positive integer). The "Surface Treatment" column indicates the type of polarizing plate used as the adherend in the adhesion test.
[0063] [Table 3]
[0064] The surface protection films of Examples 1 to 6 had an adhesive strength of 0.03 to 0.05 N / 25 mm (e.g., 0.01 to 0.1 N / 25 mm) at a slow peel speed of 0.3 m / min and an adhesive strength of 0.4 to 0.6 N / 25 mm (e.g., 1.0 N / 25 mm or less) at a fast peel speed of 30 m / min against the adherend (polarizing plate), and thus had appropriate adhesive strength and excellent adhesive performance. In addition, the surface protective films of Examples 1 to 6 had a surface resistivity of the pressure-sensitive adhesive layer of 1.0×10 +12 The peeling charge voltage of the adhesive layer against a low refractive index layer formed using a composition for forming a low refractive index layer containing a fluorine compound was in the range of -0.3 to +0.3 kV, indicating excellent antistatic performance. Furthermore, the surface protective films of Examples 1 to 6 did not stain the adherend, the polarizing plate, even after storage for 3 days and 30 days, and were also excellent in stain resistance. That is, the evaluation results shown in Table 3 for the surface protection films of Examples 1 to 6 demonstrate that the problems of the present invention were solved.
[0065] In the surface protection films of Comparative Examples 1 to 3, a liquid ionic compound was used as the (G) antistatic agent, and therefore the surface resistivity of the pressure-sensitive adhesive layer was high and the stain resistance was poor. Furthermore, the surface protection films of Comparative Examples 1 and 2 had high surface resistivity of the pressure-sensitive adhesive layer, and therefore had high peeling electrification voltage. Although the peeling electrification voltage of the surface protection film of Comparative Example 3 was not measured, it is presumed that the peeling electrification voltage was high because the surface resistivity of the pressure-sensitive adhesive layer was high. Furthermore, in the surface protection film of Comparative Example 2, the glass transition temperature of the acrylic polymer contained in the adhesive composition exceeded 0°C (calculated value: +2°C). This resulted in poor adhesive performance and excessive adhesive strength. The acrylic polymer used in Comparative Example 2 contained a high proportion of methyl acrylate and acrylic acid, which have homopolymer glass transition temperatures of high values (exceeding 0°C). Thus, the surface protection films of Comparative Examples 1 to 3 could not solve the problems of the present invention.
Claims
1. A pressure-sensitive adhesive composition comprising an acrylic polymer, an antistatic agent, and (D) a crosslinking agent, The acrylic polymer is (a1) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4, and (a2) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C5 to C18, in a ratio of 1 to 50 parts by weight, wherein the total of 1 to 50 parts by weight of the (a1) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C1 to C4 and 50 to 99 parts by weight of the (a2) at least one (meth)acrylic acid ester monomer having an alkyl group with a carbon number of C5 to C18 is 100 parts by weight; (B) at least one copolymerizable vinyl monomer containing a hydroxyl group; (C) at least one polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer, (However, acrylic polymers having at least one of a nitrogen-containing vinyl monomer not containing a hydroxyl group or an alkoxy-containing alkyl (meth)acrylate monomer copolymerized therewith are excluded.) The (a2) (meth)acrylic acid ester monomer having an alkyl group with a carbon number of 5 to 18 is at least one selected from the group consisting of isooctyl acrylate, isononyl acrylate, and 2-ethylhexyl acrylate, the (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer has a diester content of 0.2% or less, the (C) polyalkylene glycol chain-containing mono(meth)acrylic acid ester monomer contains at least one selected from the group consisting of polyalkylene glycol mono(meth)acrylate, methoxypolyalkylene glycol (meth)acrylate, and ethoxypolyalkylene glycol (meth)acrylate in an amount of 1 to 50 parts by weight per 100 parts by weight of the (A) at least two or more (meth)acrylic acid ester monomers having an alkyl group with a carbon number of 1 to 18, The acrylic polymer has a glass transition temperature of 0° C. or less, the (D) crosslinking agent is a tri- or higher functional isocyanate compound, the antistatic agent is an ionic compound having a melting point of 25° C. or higher and composed of a cation and an anion, the anion being one selected from the group consisting of a trifluoromethanesulfonate anion, a pentafluoroethanesulfonate anion, a heptafluoropropanesulfonate anion, and a nonafluorobutanesulfonate anion; the pressure-sensitive adhesive composition further comprises (E) a crosslinking accelerator which is a metal chelate compound; and (F) a keto-enol tautomer compound; The pressure-sensitive adhesive composition comprises, as an essential component, 0.01 to 10 parts by weight of the antistatic agent relative to 100 parts by weight of the acrylic polymer.
2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the cation is one selected from the group consisting of pyridinium, imidazolium, phosphonium, sulfonium, pyrrolidinium, guanidinium, ammonium, isouronium, thiouronium, piperidinium, pyrazolium, methylium, lithium, and morpholinium.
3. 3. A pressure-sensitive adhesive film comprising a resin film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition according to claim 1 or 2 laminated on one side of the resin film.
4. A surface protection film for a polarizing plate, comprising the pressure-sensitive adhesive film according to claim 3 .
5. 3. An optical film with a pressure-sensitive adhesive layer, comprising an optical film and a pressure-sensitive adhesive layer formed by crosslinking the pressure-sensitive adhesive composition according to claim 1 or 2 laminated on at least one surface of the optical film.
Citation Information
Patent Citations
Surface protective film for liquid crystal display panel
JP1999070629A
Antistatic pressure-sensitive adhesive composition
JP2000129235A
Optical adhesive and optical adhesive sheet using the same
JP2011037927A
Adhesive composition and surface protective film
JP2015105299A
Antistatic surface protective film
JP2015131414A